1991
DOI: 10.1111/j.1432-1033.1991.tb16161.x
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of the support material for enzymatic synthesis in organic media

Abstract: Enzymes were deposited on different porous support materials and these preparations were used to catalyze reactions in organic media. Reactions were carried out at specific water activities, achieved by equilibrating both the enzyme preparation and the substrate solution at the desired water activity before mixing them and thereby starting the reactions. The reaction rates obtained at the same water activity with different supports differed greatly, indicating a direct influence of the support on the enzyme. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
5

Year Published

1993
1993
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(37 citation statements)
references
References 17 publications
1
31
0
5
Order By: Relevance
“…However, the experiment suggests that initial rates in hydrocarbons are great. Intuitively water -when formed as a reaction product -needs not be dissolved in the 'bulk' solvent phase, but can instead be adsorbed by the aqueous surface layer on the protein, consistent with previous experimental [56] and theoretical [57,58] results. That allows water to 'escape' from the medium, and it may promote water formation.…”
Section: <Figure 4>supporting
confidence: 76%
“…However, the experiment suggests that initial rates in hydrocarbons are great. Intuitively water -when formed as a reaction product -needs not be dissolved in the 'bulk' solvent phase, but can instead be adsorbed by the aqueous surface layer on the protein, consistent with previous experimental [56] and theoretical [57,58] results. That allows water to 'escape' from the medium, and it may promote water formation.…”
Section: <Figure 4>supporting
confidence: 76%
“…The kinetic constants of the various forms of lipase from Pseudomonas cepacia were measured as a function of the water activity of the reaction medhim, since it has been demonstrated that it is this parameter and not the mere water concentration that determines enzyme properties (Goderis et al, 1987;Klibanov, 1989;Adlercreutz, 1991;Valivety et a1.,1992).…”
Section: Resultsanddiscussionmentioning
confidence: 99%
“…This increase is accompanied by a large increase in catalytic activity [7] and in the internal flexibility of the enzyme 18, 91. In the last few years, different experimental approaches have been used to determine how many water molecules an enzyme requires to express its activity and to what extent the protein globule has to be hydrated to maintain its maximum conformational stability [ 10, 111.…”
mentioning
confidence: 99%